Diagnóstico do serviço de abastecimento de água segundo a percepção do usuário no município de Jaguaruana–CE - Carvalho, Francisca Evânia de (Universidade Federal Rural do Semi-Árido, 2018)
Waterisessentialandvitallyimportanttothelifeandeconomicandsocialdevelopment of a nation. The water supply in a municipalityshould aim to distribute water to the community for which it was designed, in quantity and quality, so that it has adequate pressure and is drinkable withoutrisks to theconsumer’s health. describe and analyzethe water supplyservice ofthemunicipalityofJaguaruana-CE,emphasizingtheuser’sopinionofthesystem. Forthis,a documentaryandﬁeldresearchwascarriedout. DatafromtheCearáWaterandSewerCompany (CAGECE), Brazilian Institute of Geography and Statistics (IBGE), Ceará State Regulatory Agency(ARCE)wereused. Inaddition,thedatawereobtainedthroughquestionnaireapplication to the population of the municipality that has access to water from the water supply system (SAA), covering nine neighborhoods and two communities, and the application was made at random. Data were then tabulated in Excel spreadsheets (version 2015), and later, subjected to descriptive statistical analysis. Considering the data obtained, it is observed that the majority of users of the system are satisﬁed with the service provided by CAGECE, since the system generally operates continuously, meeting theneedsof its users.
Monografia
Keywords: Importância da água; Consumidor; Descrição do Sistema de Abastecimento; Importanceof water; Consumer; Descriptionof the SupplySystem; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA